2015
DOI: 10.4238/2015.november.13.4
|View full text |Cite
|
Sign up to set email alerts
|

Cartilage oligomeric matrix protein and matrix metalloproteinase-3 expression in the serum and joint fluid of a reversible osteoarthritis rabbit model

et al.

Abstract: ABSTRACT. The main pathological characteristic of osteoarthritis (OA) is cartilage damage. We explored cartilage oligomeric matrix protein (COMP) and matrix metalloproteinase-3 (MMP-3) changes during articular cartilage injury and repair. Rabbits were randomly divided into the following: a blank control group; groups M1, M2, and M3, in which breaking was performed for 2, 4, and 6 weeks, respectively; and groups L1, L2, and L3, in which breaking was discontinued for 2, 4, and 6 weeks, respectively, following a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 21 publications
1
10
0
Order By: Relevance
“…Approximately 10 mL of whole blood was collected from the vena cava at euthanization, and the serum was separated by centrifugation at 3000 rpm for 10 min. Serum concentrations of COMP, CTX-II, and MMP-3 were measured using sandwich enzyme-linked immunosorbent assays (ELISAs) in accordance with previous reports [15,16]. A rabbit COMP ELISA kit (MBS721182, MyBioSource, San Diego, CA, USA), rabbit CTX-II ELISA kit (MBS705896, MyBioSource, San Diego, CA, USA) and rabbit MMP-3 ELISA kit (MBS2502146, MyBioSource, San Diego, CA, USA) were used in this measurement.…”
Section: Measurement Of Serum Comp Ctx-ii and Mmp-3 Levelsmentioning
confidence: 87%
See 4 more Smart Citations
“…Approximately 10 mL of whole blood was collected from the vena cava at euthanization, and the serum was separated by centrifugation at 3000 rpm for 10 min. Serum concentrations of COMP, CTX-II, and MMP-3 were measured using sandwich enzyme-linked immunosorbent assays (ELISAs) in accordance with previous reports [15,16]. A rabbit COMP ELISA kit (MBS721182, MyBioSource, San Diego, CA, USA), rabbit CTX-II ELISA kit (MBS705896, MyBioSource, San Diego, CA, USA) and rabbit MMP-3 ELISA kit (MBS2502146, MyBioSource, San Diego, CA, USA) were used in this measurement.…”
Section: Measurement Of Serum Comp Ctx-ii and Mmp-3 Levelsmentioning
confidence: 87%
“…Kuhne et al [75] reported that the serum COMP level in serum increases in patients after traumatic knee injury. COMP may be instructive regarding cartilage degradation status, and has been used as a marker of OA [15,16,76]. This protein is a constituent of AC, but is also synthesized by tendon synoviocytes and fibroblasts [76,77].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations